Recent developments in crosslinking of elastomers - Aprem Abi Santhosh; Joseph Kuruvilla; Sabu Thomas (Rubber Chemistry and Technology, 2005)
The recent developments in the vulcanization of elastomers, major types of crosslinking, and mechanism of crosslinking have been reviewed. Attention has been made to sum up the accelerated vulcanization. Possible mechanisms by which the reaction is taking place are discussed. The role of accelerators, activators, and fillers has been described. The different types of crosslinks and importance of each type on the specific properties of the resulting vulcanizates etc.,are discussed. Various aspects of vulcanization like model compound vulcanization, nitrosamine generation, etc.,are discussed. The importance of binary accelerators and possible mechanism of their action have been mentioned. The method of double network formation, which is useful for the improvement in properties, is also described. The different methods for characterization of networks and different methods for estimating crosslink densities are also explained.
Keywords: Accelerators; Crosslinking; Elastomers; Vulcanization